RESEARCH ON THE DEVELOPMENT AND IMPLEMENTATION OF AUGMENTED REALITY TECHNOLOGIES IN THE EDUCATIONAL PROCESS - Sarsimbayeva S.M.; Mukasheva M.U.; Shuinshina Sh.M.; Dimitrov V.T. (Scientific Journal of Pedagogy and Economics, 2020)
The article deals with the development of augmented reality applications on the Vuforia platform, as well as the use of augmented reality technology in the educational process for the purpose of visual modeling of educational material to Supplement the material with visual information. The results of the analysis of existing approaches to the development of augmented reality applications, platforms, tool development environments such as Vuforia, with the ability to connect Unity, and the implementation of augmented reality technology are shown. The importance of using high-level augmented reality technologies, the prospects for using augmented reality technology, and the opportunities and advantages of using it in the educational process are highlighted. It is noted that the situation in the field of education determines the relevance of the use of new information technologies in the field of education and one of the promising areas of development of innovative educational technologies is the use of augmented reality in the learning process. An augmented reality application to great Kazakh poet Abay Kunanbayev’s poems created on the basis of marker technology is proposed.